2020
DOI: 10.1021/acs.iecr.0c01095
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Encapsulated ZSM-5 Zeolite with Nanosheet-Assembled Structure for the Selective Catalytic Reduction of NOx with NH3

Abstract: A series of iron-encapsulated hierarchical ZSM-5 zeolites with nanosheet-assembled structure were designed and successfully fabricated, and their catalytic performance was investigated for the selective catalytic reduction of NO x with NH 3 (NH 3 -SCR). Because of the synergy between the welldispersed Fe active species and the Brønsted acidic framework of zeolites, the Fe-containing ZSM-5 catalyst displayed excellent catalytic performance, and density functional theory (DFT) calculation data indicated that cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Many zeolites with various framework types, such as MFI, BEA, CHA, AEI, ERI, KFI, AFX, DDR, RTH, SFW, LEV, LTA, RHO, and UFI, have been investigated as SCR catalysts [3][4][5][6][7][8]. Iwamoto et al [9,10] first reported the catalytic activity of Cu-ZSM-5 for the decomposition of NO.…”
Section: Introductionmentioning
confidence: 99%
“…Many zeolites with various framework types, such as MFI, BEA, CHA, AEI, ERI, KFI, AFX, DDR, RTH, SFW, LEV, LTA, RHO, and UFI, have been investigated as SCR catalysts [3][4][5][6][7][8]. Iwamoto et al [9,10] first reported the catalytic activity of Cu-ZSM-5 for the decomposition of NO.…”
Section: Introductionmentioning
confidence: 99%
“…% H 2 O and 500 ppm SO 2 [99] . Significant sulfur resistance was reported also for other catalysts, including Fe‐encapsulated ZSM‐5 zeolite with nanosheet‐assembled structure [143] and Pr x Mn 1‐ x O δ /3DOM ZSM‐5 [144] …”
Section: Micro‐/mesoporous Zsm‐5‐based Catalystsmentioning
confidence: 76%
“…% H 2 O and 500 ppm SO 2 . [99] Significant sulfur resistance was reported also for other catalysts, including Fe-encapsulated ZSM-5 zeolite with nanosheet-assembled structure [143] and Pr x Mn 1-x O δ /3DOM ZSM-5. [144] Although in some of the above studies the authors (e. g., [130,140,141] ) claimed that the presence of mesopores can enable faster transport of the reactants to active sites this proposal has not been confirmed experimentally.…”
Section: Micro-/mesoporous Zsm-5-based Catalystsmentioning
confidence: 88%
“…XRD analysis was performed to investigate the crystal structures of the catalyst samples (not shown). The diffraction peaks at 2θ of 7.9°, 8.8°, 23.1°, and 23.8° were detected in all samples, which are attributed to characteristic diffraction signals of the ZSM-5 zeolite [6] , illustrating that the catalysts maintained the original crystal structure of the ZSM-5 zeolite.…”
Section: Xrd and Bet Analysismentioning
confidence: 81%